PENDIDIKAN LUAR SEKOLAH DAN PEMBANGUNAN MANUSIA INDONESIA - Engking Soewarman Hasan; Sri Nurhayati (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2012)
Indonesia today is still struggling to find the best way in developing its human resources. The essence of human development according to Tilaar (1998:107) is the development of dignity and human quality, and to develop human dignity and quality is to give them choices, so the role of education is very vital in giving human the ability to choose and to widening their horizons on what they need to choose. According to National Education System Law No. 23, there are three lines of education: formal, nonformal, and informal education. Coombs (1973) defines nonformal education as every organized and sistematic activity outside the well-established schooling system, conducted independently or as part of wider activity, and intended to serve specific students in order to achieve their learning goals (Sudjana, 2004:22). This paper aims at providing information on how nonformal education has become the answer of today’s struggling of Indonesia in developing its human resources.